2016
DOI: 10.4028/www.scientific.net/amm.852.118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steel Shots Size on Tensile Properties of Magnetic Moulded MMC

Abstract: The Magnetic moulding process is an extension of lost foam process, in which an Expendable Poly Styrene (EPS) pattern is surrounded by steel shots bonded together by the action of an induced electromagnetic field. Magnetic moulding is a potential alternative for conventional sand casting, which has disadvantages like low thermal conductivity and low permeability, which affects the metallurgical and mechanical properties of the casting. In the present work Al/SiCp metal matrix composite (MMC) samples are moulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…In addition, this coating has the optimum permeability for the hot gases to escape. Steel shots of 0.6 mm diameter were selected as it is the optimum size for producing better properties of the cast [20]. The current induced in the coil was around 5 A for about 30 s, as beyond this time, overheating of the coil occurs, resulting in coil damage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this coating has the optimum permeability for the hot gases to escape. Steel shots of 0.6 mm diameter were selected as it is the optimum size for producing better properties of the cast [20]. The current induced in the coil was around 5 A for about 30 s, as beyond this time, overheating of the coil occurs, resulting in coil damage.…”
Section: Resultsmentioning
confidence: 99%
“…Following the definition of the magnetic field module, the heat transfer module was set up, where the aluminium domain was defined as the phase change medium with 360 kJ/kg as the latent heat of fusion and 933.47 K as the phase transition temperature; the steel shots domain was defined as a porous media with a porosity value of 0.6 mm (Table 2). Ronald et al studied the influence of steel shots on the properties of the cast and found that steel shots of 0.6 mm produced a cast with better mechanical properties when compared with 0.1 mm and 1 mm steel shots [20]. Hence, steel shots of 0.6 mm were chosen as the mould material for magnetic moulding in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation